Sequencing and characterization of complete mitogenome DNA for Rasbora myersi (Cypriniformes: Cyprinidae: Rasbora) and its evolutionary significance - Chung, Hui Hui; Whye, Leonard Kit Lim; Roja, Jill Sela; Cynthia Keranti, Anak Kamar; Liaob, Yunshi; Lam, Tommy Tsan-Yuk; Chong, Yee Ling (Elsevier Ltd., 2019)
The Seluang fish (Rasbora myersi) is a small ray-finned fish categorized under the genus Rasbora in the Cyprinidae family. In this study, the complete mitogenome sequence of R. myersi was sequenced using two primer pairs targeting overlapping regions. The mitogenome is 16,581 bp in length, encompassing 22 transfer RNA genes, 13 protein-coding genes, two ribosomal RNA genes and a putative control region. Identical gene organisation was observed between this species and other genus counterparts. The heavy strand accommodates 28 genes while the light strand houses the other nine genes. Most protein-coding genes utilize ATG as start codon, excluding COI gene, which employs GTG instead. The central conserved sequence blocks (CSB-F, CSB-E and CSB-D), variable sequence blocks (CSB-3, CSB-2 and CSB-1) as well as the terminal associated sequence (TAS) are conserved within the control region. The R. myersi formed a trio with R. borapetensis and R. argyrotaenia in a moderately strong clade with bootstrap value of 86. This work acts as essential gateway towards further molecular evolution and population genetics studies of the Rasbora genus in future.